A2.23 Deregulated, IFNA driven autophagy shapes the phenotype of autoreactive SLE monocytes. (13th February 2015) - Gkirtzimanaki, K; Kabrani, E; Sidiropoulos, P; Bertsias, G; Boumpas, D; Verginis, P
Abstract : Background/Objectives: In SLE circulating IFNa can induce peripheral blood monocytes to differentiate into dendritic cells with increased MHCII antigen presenting capacity. Monocytes' differentiation and self-antigen presentation has been shown to depend on autophagy, the catabolic degradation of unnecessary/dysfunctional cellular components and organelles and relies on the cooperation of autophagosomes with lysosomes. Our aim was to delineate the role of autophagy in shaping the autoreactive phenotype of SLE monocytes upon IFNa signalling and to dissect the underlying mechanism. Materials/Methods: Serum and peripheral blood CD14 + monocytes were isolated from active, newly diagnosed or off-treatment SLE patients (n = 20) and age and sex matched healthy donors (n = 18). Autophagy, both spontaneous and following incubation with SLE serum (10%) or rhIFNa (10 4 U/ml), was assessed by immunoblotting and confocal microscopy for LC3 and P62. ATG5 and P62 mRNA levels were assessed by QPCR. Autophagy induction was inhibited by wortmanin or 3MA and autophagy completion was inhibited by hydroxychloroquine. Rapamycin and LPS were used as autophagy inducers. Healthy monocytes were treated with SLE serum or rIFNa and their antigen presenting capacity was assessed by flow cytometry for HLA-DR, CD86 and CD40. Alterations in autophagolysosomal pH were assessed by confocal microscopy (Lysotracker Red-DND99). ROS production was measured using DCFHDA and mitochondrial polarisation was assessed by MitotrackerRed CMXRos and JC1. Results: SLE monocytes exhibited increased levels of Atg5 mRNA (3 ± 0.5 fold increase, p < 0.05) and lipidated LC3B protein (p < 0.005) compared to healthy controls. Notably, autophagosomal P62 degradation was defective in SLE and this coincided with defective lysosomal acidification. Treatment of healthy monocytes with SLE serum or rIFNa recapitulated the abnormalities observed in SLE monocytes as for ATG5 transcription (p < 0.005), LC3B lipidation (p < 0.05), defective autophagosomal P62 degradation (p < 0.05) and defective lysosomal acidification. Importantly, in both SLE monocytes and healthy monocytes treated with rIFNa, mitochondria were found hyperpolarized and ROS production was increased. Enhanced antigen presenting capacity upon SLE serum or IFNa treatment was autophagy dependent as evidenced by autophagy manipulation experiments. Conclusions: Monocytes from SLE patients display enhanced autophagy induction, driven by soluble factors such as IFNa. Autophagy completion is disrupted and this coincides with the presence of uncleared hyperpolarized mitochondria, increased cellular oxidative status and defective lysosomal acidification. Under these conditions, the antigen presenting capacity of human monocytes is increased and depends on autophagic alterations. Further studies will address whether deregulated autophagy/mitophagy completion is involved in the generation of an endogenous source of self antigens and whether this leads to SLE characteristic autoimmune phenotype of monocytes.